THE MAIN PLACE OF IDEOLOGY IN PUBLIC LIFE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
This article examines the emergence of ideology in society, a conceptual analysis ofthe previous theory of ideology in the scientific aspect, with a full-fledged study of its objects, andresearch problems in the humanities.
Keywords: society, ideology, phenomenon, philosophy, economics, personality, culture, formation, social.